2005
DOI: 10.1212/01.wnl.0000163767.99354.c3
|View full text |Cite
|
Sign up to set email alerts
|

A new botulinum toxin type A free of complexing proteins for treatment of cervical dystonia

Abstract: A new botulinum toxin type A free of complexing proteins (NT 201) was compared with BOTOX in patients with cervical dystonia by means of a double-blind noninferiority trial. Four hundred sixty-three patients received IM injections of 70 to 300 U of NT 201 or BOTOX and were followed up over 16 weeks. The study clearly shows that NT 201 is at least as effective and safe as BOTOX.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
197
0
11

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(225 citation statements)
references
References 4 publications
17
197
0
11
Order By: Relevance
“…Despite differences in specific neurotoxin activity (defined as the biologic activity in units per mass of neurotoxin protein), clinical studies have shown that the efficacy of Xeomin Ò and Botox Ò is comparable. [10][11][12] Dressler and colleagues [13] also showed an equivalent potency of Botox Ò and Xeomin Ò in a mouse LD 50 bioassay. Together, these results demonstrate that the amount of neurotoxin in Botox Ò and Xeomin Ò exhibits the same activity in the clinical environment as in the standard mouse in vivo assay.…”
Section: Elisa Specificitymentioning
confidence: 99%
See 1 more Smart Citation
“…Despite differences in specific neurotoxin activity (defined as the biologic activity in units per mass of neurotoxin protein), clinical studies have shown that the efficacy of Xeomin Ò and Botox Ò is comparable. [10][11][12] Dressler and colleagues [13] also showed an equivalent potency of Botox Ò and Xeomin Ò in a mouse LD 50 bioassay. Together, these results demonstrate that the amount of neurotoxin in Botox Ò and Xeomin Ò exhibits the same activity in the clinical environment as in the standard mouse in vivo assay.…”
Section: Elisa Specificitymentioning
confidence: 99%
“…Indeed, the most informative comparisons of BoNT/A containing products have been made in clinical studies. In a 16-week, randomized, double-blind, non-inferiority trial in 463 patients with cervical dystonia, [10] Xeomin Ò was shown to be as effective as Botox Ò with a comparable adverse event profile when a clinical conversion ratio of 1 U : 1 U was used. Moreover, in a double-blind, noninferiority trial in 300 patients with blepharospasm, treatment with Xeomin Ò was as effective as and as safe as Botox Ò (using a 1 U : 1 U conversion ratio) when assessed by the Jankovic Rating Scale.…”
mentioning
confidence: 99%
“…30 In another Dysport/Botox study using two ratios of 3:1 and 4:1, patients who received Dysport had more improvement in terms of pain and neck posture, but showed more side effects. 31 The Xeomin/Botox study 32 showed no difference between the two in terms of improvement of total TWSTRS score and TWSTRS pain score. Both BoNTs displayed the same frequency of side effects in this study.…”
Section: Medical Treatmentmentioning
confidence: 95%
“…BoNT-A (Dysport), 30,31 one compared Botox with BoNT-A (Xeomin), 32 and one compared Botox with BoNT-B (Myobloc). 33 One of the two Dysport/Botox studies in CD showed comparable efficacy and side effects when the investigators used the ratio of three Dysport units to one Botox unit.…”
Section: Medical Treatmentmentioning
confidence: 99%
“…In klinischen Studien konnte für BoNT/A und BTXCo2/3 in den Indikationen Torticollis spasmodicus und Blepharospasmus eine Dosisäquivalenz dokumentiert werden [2,16,29]. Die empfohlene Dosierung von BTXCo2 wurde in dieser Studie daher 1:1 auf BoNT/A über-tragen.…”
Section: Introductionunclassified